Dwelling and Clothing as Metaphors for the Human Body in 2 Cor 5:1–4 - Franciszek Mickiewicz (The Biblical Annals, 2022)
There is an allegory of the human body in 2 Cor 5:1–4 that is discussed by many scholars and has many different interpretations. The author of this article joins this discussion and tries to answer the question of what the theological message of this pericope is. The metaphors that make it up can be divided into two groups: 1) home metaphors; 2) metaphors of putting on and taking off of clothes. In his text, Paul arranges them in an antithetical way and refers to two stages of human life: the earthly life of believers, which a person leads in a destructible body and which ends in death, and the future condition of believers, which begins with the reception of the resurrection body. The analysis carried out in the article leads to the conclusion that, in his reflection, Paul does not write anything about the intermediate state which is referred to by the followers of Platonic and Gnostic thought in the Hellenistic environment. He eagerly wishes to stand before the Lord during the Parousia without losing his mortal body in order to pass to eternal life without the experience of death by putting on the glorious body.